Differences in soil physicochemical properties and rhizosphere microbial communities of flue-cured tobacco at different transplantation stages and locations - Zhao, Leifeng; He, Yuansheng; Zheng, Yuanxian; Xu, Yinlian; Shi, Shoujie; Fan, Meixun; Gu, Shaolong; Li, Guohong; Tianli, Wajie; Wang, Jiming; Li, Junying; Deng, Xiaopeng; et al. (Frontiers in Microbiology, 2023)
Rhizosphere microbiota play an important role in regulating soil physical and chemical properties and improving crop production performance. This study analyzed the relationship between the diversity of rhizosphere microbiota and the yield and quality of flue-cured tobacco at different transplant times (D30 group, D60 group and D90 group) and in different regions (Linxiang Boshang (BS) and Linxiang ZhangDuo (ZD)) by high-throughput sequencing technology. The results showed that there were significant differences in the physicochemical properties and rhizosphere microbiota of flue-cured tobacco rhizosphere soil at different transplanting times, and that the relative abundance of Bacillus in the rhizosphere microbiota of the D60 group was significantly increased. RDA and Pearson correlation analysis showed that Bacillus, Streptomyces and Sphingomonas were significantly correlated with soil physical and chemical properties. PIGRUSt2 function prediction results showed that compared with the D30 group, the D60 group had significantly increased metabolic pathways such as the superpathway of pyrimidine deoxyribonucleoside salvage, allantoin degradation to glyoxylate III and pyrimidine deoxyribonucleotides de novo biosynthesis III metabolic pathways. The D90 group had significantly increased metabolic pathways such as ubiquitol-8 biosynthesis (prokaryotic), ubiquitol-7 biosynthesis (prokaryotic) and ubiquitol-10 biosynthesis (prokaryotic) compared with the D60 group. In addition, the yield and quality of flue-cured tobacco in the BS region were significantly higher than those in the ZD region, and the relative abundance of Firmicutes and Bacillus in the rhizosphere microbiota of flue-cured tobacco in the BS region at the D60 transplant stage was significantly higher than that in the ZD region. In addition, the results of the hierarchical sample metabolic pathway abundance map showed that the PWY-6572 metabolic pathway was mainly realized by Paenibacillus, and that the relative abundance of flue-cured tobacco rhizosphere microbiota (Paenibacillus) participating in PWY-6572 in the D60 transplant period in the BS region was significantly higher than that in the ZD region. In conclusion, different transplanting periods of flue-cured tobacco have important effects on soil physical and chemical properties and rhizosphere microbial communities. There were significant differences in the rhizosphere microbiota and function of flue-cured tobacco in different regions, which may affect the performance and quality of this type of tobacco.